Skånskt Naturbeteskött, Närproducerat nötkött - Nilsson, Johanna (2008)
Skånskt Naturbeteskött is a group of approximately 30 beefproducers in the south of Sweden, who sell their products on the local market. They are certified with Svenskt Sigill, an organisation that works with animal welfare, environmental responsibility, safe food, open landscape and independent qualitycontrol. These producers have to fulfil certain demands regarding pasture and quality of the meat. For this essay I did a market investigation in which I wanted to find out what qualities the Swedish market and the consumers want in their beef. The purpose was to find out what Skånskt Naturbeteskött could do differently to satisfy the market for locally produced beef in the south of Sweden.